FAKTOR-FAKTOR PENYEBAB RENDAHNYA KINERJA GURU DAN KORELASINYA TERHADAP PEMBINAAN SISWA: Studi kasus di SMAN 1 Darul Imarah Aceh Besar - Srinalia Srinalia (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2015)
The issue of teacher’s performance has become a central point which is interesting to discuss by many people today. The fact shows that most teachers of SMAN 1 Darul Imarah, Aceh Besar, do not participate in coaching students effectively. This research employed qualitative descriptive approach. The research subjects were teachers and principals at SMAN 1 Darul Imarah, Aceh Besar. The results showed that low levels of teacher’s performance to student development is influenced by internal factors, namely the ability and motivation of teachers and the external factors are influenced by the physical working environment , and principal’s management. Teachers of SMAN 1 Darul Imarah, Aceh Besar, have not been fully able to motivate, nurture, and guide students in order to achieve effective learning.